Colonic obstruction after ingested gravel and stone - P.V. Narayanan (Asian Journal of Surgery, 2012)
This case concerns a 10-year-old boy with a history of behavioral abnormality that arrived at our surgical emergency room with acute abdominal discomfort. The boy had acute colitis-like clinical symptoms resulting from ingested and retained foreign bodies in the colon. These foreign bodies (gravel and stones) had accumulated in the entire colon over a period of 1 year. Attempts to dislodge the foreign bodies from the rectum by mechanical means failed; therefore the possibility of surgical intervention was considered in view of the worsening colitis. However, the problem was finally resolved by repeated basketting by colonoscopy, antibiotics and later laxatives. The case is noteworthy because of the extent of the condition, difficulty of the decision-making, and the relative success of watchful conservative measures.